The establishment of the IIUM as explained by Mahathir Mohamad - Syed Azamthullah, Syed Salim Agha (IIUM Press, 2009)
By the Grace and Mercy of Allah s.w.t, the long-held aspiration and hope of Muslims in Malaysia, and in particular, of the illustrious alumni of Kolej Islam Malaya of having an Islamic University in Malaysia became a reality when Dato' Dr. Mahathir Mohamad (now Tun Dr. Mahathir Mohamad) the then Prime Minister of Malaysia announced in January 1982 in the United Arab Emirates that Malaysia had decided to establish the International Islamic University Malaysia. The announcement was made in Abu Dhabi when the Prime Minister visited H.H. Sheikh Zayed Bin Sultan Al Nahyan.